Uso de Biofiltros para remoção de cromo (VI) - Leles, Daniela Martins Araujo (2010)
This work studied the biological reduction of Cr (VI) and total chromium removal in anaerobic filter followed by a submerged biofilter with intermittent aeration, using mixed culture of microorganisms. For the work were obtained two mixed cultures, one of the sludge of AMCOA (Association of Manufacturers of Leather and Related from the Industrial District of Franca/SP) and another of DMAE (Municipal Department of Water and Sewer from the city of Uberlândia/MG). In preliminary tests of the adaptation of mixed culture to hexavalent chromium, both shown promise. After, was made a central composite design (CCD) with three variables and using the following concentrations: sodium acetate (0,6 to 11,412 g/L), ammonium chloride (0,06 to 1,141 g/L) and chromium (VI) (2,34 to 137,35 mg/L). The CCD evaluated the bioreduction of Cr (VI) and removal of TOC (Total Organic Carbon). For the answer bioreduction of chromium (VI), it was obtained (85,23% of reduction to the initial concentration of chromium (VI) from 137,35 mg/L) and it was verified that lower concentrations of sodium acetate (0 to 6 g/L) and higher ones of ammonium chloride (0,5 to 1 g/L) favors the reduction of chromium six, being the initial concentration of chromium six the variable of major effect in the response. For the response removal of TOC, the concentration range that maximizes the response was: sodium acetate from 4 to 8 g/L, ammonium chloride higher than 0,8 g/L and concentration of chromium six between 60 and 100 mg/L. The ammonium chloride was the variable of greater effect on the removal of TOC. From CCD were selected the following concentrations to the study of kinetics: 6 g/L of sodium acetate and 1 g/L of ammonium chloride and initial concentrations of chromium six from 120, 150 and 180 mg/L. The results showed to the kinetics with concentration of 120 mg/L of chromium six, after 168 hours of operation in the reactors, there isn t the saturation of the same and the removal of chromium six and total was the 100% and the TOC was the 87,5%. In the kinetics with 150 mg/L of chromium six, within the operating time studied, the output of chromium (six and total) in the aerobic reactor occurred after 166 hours of operation and the saturation of anaerobic reactor occurred after 150 hours, and in aerobic reactor didn t occurred saturation.. In kinetics with 180 mg/L, there was saturation of two reactors, in the anaerobic after 190 hours of operation and in the aerobic after 225 hours. In the kinetics with 150 and 180 mg/L of Chromium six initial, the results showed there was cell death with lise of cells, due to reduction of biomass concentration and increase of TOC. For the initial concentrations of 150 and 180 mg/L, the models of Michaelis-Menten and Largergren described well the experimental datas, for the retention of Chromium ((VI) and total), also was observed breach of beds. After each kinetics, including those that occurs the saturation of reactor concerning to the chromium, the concentration of microorganisms came back to values near of initials ones, showing that the biomass came back to grow inside the reactors. After the kinetics with 150 and 180 mg/L of chromium six, the necessary time for the output of chromium come back to the initial values (zero) was 108 hours. The use of mixed culture in anaerobic biofilters followed by another one submerged aerobic with intermittent aeration showed be promising to the removal of chromium.